2020
DOI: 10.3390/f11090979
|View full text |Cite
|
Sign up to set email alerts
|

Linking Forest Vegetation and Soil Carbon Stock in Northwestern Russia

Abstract: Research Highlights: It was found that both tree species and ground vegetation affected soil carbon stock in boreal forests. Carbon stocks in the mineral layers were related negatively to the C/N ratio in the organic horizon and pine proportion in the growing stock volume, and positively to the share of herbaceous plants and the proportion of spruce. Background and Objectives: Existing research showed the effects of tree species on soil carbon stocks in organic horizons, but these effects were less clear in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
(55 reference statements)
0
14
1
1
Order By: Relevance
“…The positive correlation between the LFH horizon of the spruce stand and standing dead wood may suggest increased input of litter to the LFH horizon from the dying crown compartment, which support the SOC accumulation in the LFH layer. Altogether, this may affect the stocks as well as the stability of the SOC (Vesterdal et al 2013, Lukina et al 2020, and thus the long-term storage of SOC in the forest N is the major limiting factor for tree growth in boreal forests, and N limitation typically constrains the buildup of C (Tamm 1991(Tamm , H ögberg et al 2017. Contrary to our hypothesis, the tree species change did not significantly increase the total N stocks in the soil down to 1 m soil depth, nor did the planting of Norway spruce promote an allocation of N from the mineral soil to the forest floor.…”
Section: Ecosystem C and N Stocks And Interactionsmentioning
confidence: 99%
“…The positive correlation between the LFH horizon of the spruce stand and standing dead wood may suggest increased input of litter to the LFH horizon from the dying crown compartment, which support the SOC accumulation in the LFH layer. Altogether, this may affect the stocks as well as the stability of the SOC (Vesterdal et al 2013, Lukina et al 2020, and thus the long-term storage of SOC in the forest N is the major limiting factor for tree growth in boreal forests, and N limitation typically constrains the buildup of C (Tamm 1991(Tamm , H ögberg et al 2017. Contrary to our hypothesis, the tree species change did not significantly increase the total N stocks in the soil down to 1 m soil depth, nor did the planting of Norway spruce promote an allocation of N from the mineral soil to the forest floor.…”
Section: Ecosystem C and N Stocks And Interactionsmentioning
confidence: 99%
“…However, soil carbon stock also depends on biotic factors, such as vegetation and soil biota. It has been shown that in forests of different types, variation in soil carbon stocks was related to the species composition of tree plants [1] and ground vegetation [4]. However, the question arises, what is the combined effect of different woody and herb plant species on carbon stocks?…”
Section: Introductionmentioning
confidence: 99%
“…The direct pathway of trees interacting with soil includes both leaf litter input and root release. The litterfall from woody plants is the main source of soil organic matter [27][28][29][30][31]. Tree species vary significantly in their litter quality, as well as in their litter decomposition rates [32].…”
Section: Introductionmentioning
confidence: 99%